Health risk communication message comprehension is influenced by image inclusion. (2nd October 2018) - Manno, Francis A. M.; Lively, Malcolm B.; Manno, Sinai H. C.; Cheng, Shuk H.; Lau, Condon
Abstract: The impact of images on risk communications such as public service announcements is unknown. Whether images contained within a printed message such as a food safety warning alters the comprehension of the underlying text, has not previously been explored. The present study examined three factors of a risk communication in the print form: (1) the role images play in promoting comprehension of risk messages, (2) how demographic variables such as gender impacts message reception and (3) the need for cognition, or the degree to which some individuals are innately motivated to comprehend and understand information. Examples of risk communications in the print form are warnings on food or tobacco and alcohol warnings. In the present study, students at an undergraduate university ( N  = 92, 61 females, age 19.89 (SD =1.94) years, range 18–32), read risk communications with and without images. The purpose of the study was to ascertain the affect images have on message comprehension and receptivity. Comprehension was assessed by the structural knowledge test. Negative/fear-arousing images increase message receptivity and subsequent learning when accompanying printed risk communications. Gender alone did not significantly impact message receptivity, although males tended to show greater change in structural knowledge pre- to post-test. This was true especially for the negative fear-arousing images condition. Need for cognition plays a significant role in message receptivity. Nevertheless, for risk communications illustrated with fear arousing images, it appears that the need for cognition is not a necessary condition to learn the message. Further research is needed to determine how these factors impact the degree or depth of message processing.